2018
DOI: 10.1055/s-0038-1673619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Bouts of Exercise on the Hemostatic System

Abstract: Physical activity is beneficial for health, for example, by lowering the risk of cardiovascular events. However, vigorous exercise is associated with the occurrence of thromboembolic events and sudden cardiac death, in particular in untrained individuals. Whereas acute exercise is known to cause a hypercoagulable state, repeated exposure to (strenuous) exercise by means of training may actually condition the hemostatic response to exercise. To date, the effects of exercise training on blood coagulability and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 129 publications
(157 reference statements)
0
24
0
1
Order By: Relevance
“…Alterations in hematocrit due to various conditions, such as anemia, dehydration, and polycythemia, may lead to inappropriate results (ie, PFA‐100, inappropriate citrate concentration) . Exercise may lead to increased procoagulant factors, as well as increased von Willebrand factor . Patients may also have extensive hemolysis, hyperbilirubinemia, or lipemia that can interfere with optical clot‐based detection systems .…”
Section: Biological Causes Of Spurious Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations in hematocrit due to various conditions, such as anemia, dehydration, and polycythemia, may lead to inappropriate results (ie, PFA‐100, inappropriate citrate concentration) . Exercise may lead to increased procoagulant factors, as well as increased von Willebrand factor . Patients may also have extensive hemolysis, hyperbilirubinemia, or lipemia that can interfere with optical clot‐based detection systems .…”
Section: Biological Causes Of Spurious Resultsmentioning
confidence: 99%
“…18 Exercise may lead to increased procoagulant factors, 19 as well as increased von Willebrand factor. 20 Patients may also have extensive hemolysis, hyperbilirubinemia, or lipemia that can interfere with optical clot-based detection systems. 19,21 Finally, patients may be on medications, such as heparin or direct oral anticoagulants, which can alter the results of the assay.…”
Section: Con Cep T Of Error Of Re Sults In Coag Ul Ationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased circulating active VWF levels may also be present in other conditions associated with infection and/or inflammation, for instance in chronic kidney disease (submitted). Moreover, using the current assay, we found that active VWF levels in healthy individuals increase following strenuous exercise [43]. Quantification of active VWF in a variety of diseases could provide valuable pathophysiological insight for diagnosis and development of new treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that physical activity is beneficial for health and can lower the risk of cardiovascular disease [1][2][3] ; however, vigorous exercise is associated with thromboembolic and sudden cardiac events, particularly in untrained individuals. Exploring the concept of transitioning from risk to benefit, in the first review of this issue (by van der Vorm et al), 4 the authors provide an overview of existing literature on how training programs and training status influence hemostasis in healthy individuals. Furthermore, pilot study data are presented describing the effects of repetitive submaximal intensity cycling on procoagulant and anticoagulant processes in physically fit individuals.…”
mentioning
confidence: 99%